Technical innovations for small-scale producers and households to process wet cassava peels into high quality animal feed ingredients and aflasafe™ substrate - Okike, Iheanacho; Samireddypalle, A.; Kaptoge, L.; Fauquet, Claude M.; Atehnkeng, J.; Bandyopadhyay, Ranajit; Kulakow, Peter A.; Duncan, Alan J.; Alabi, Tunrayo; Blümmel, Michael (Practical Action Publishing, 2015)
Nigeria, the world’s largest producer of cassava, harvests 54 million metric tonnes (Mt) of cassava tubers annually. More than 95 per cent of its uses require peeling which generates up to 14 Mt of waste annually; mostly due to challenges related to drying. Sun drying is practically impossible during the wet season and it takes 2–3 days in the dry season to reduce the moisture content of fresh peels from about 60 per cent to 20 per cent or less – a marketable state. This is a report on a multi-centre and multi-disciplinary research work (in its early stages) to better utilize the waste. Ongoing work is showing great potential and has so far dramatically reduced cassava peels moisture content to 12–15 per cent within six sunshine hours using only equipment in current use by small-scale processors and households. The considerably shorter processing ensures high-quality products, low in aflatoxins contamination. Also, in a small sample experiment, when compared to sorghum grains currently being used for the production of aflasafe™ as control, the pellets supported the sporulation of Aspergillus flavus up to 87.5 per cent of the control with better cost effectiveness. The research challenges remain in terms of circumventing drying technologies, creating and maintaining product quality standards, and facilitating and catalysing collective action among adopters. Nevertheless, the research carries huge potential to address feed scarcity, contribute to food security and food safety, clean up the environment, and improve the incomes and livelihoods of people currently engaged in processing cassava tuber into food – 85 per cent of them women.